2011
DOI: 10.1128/jb.00221-11
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Factor-Dependent Transcription Termination in a nusA Mutant of Escherichia coli: Spectrum of Termination Efficiencies Generated by Perturbations of Rho, NusG, NusA, and H-NS Family Proteins

Abstract: The proteins NusA and NusG, which are essential for the viability of wild-type Escherichia coli, participate in various postinitiation steps of transcription including elongation, antitermination, and termination. NusG is required, along with the essential Rho protein, for factor-dependent transcription termination (also referred to as polarity), but the role of NusA is less clear, with conflicting reports that it both promotes and inhibits the process. In this study, we found that a recessive missense nusA mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Thus, expression of any one of several dominant-negative variants of H-NS, including ⌬64, L26P, and E53G/T55P, restores the efficiency of transcription termination (that is, suppresses polarity relief) in rho and nusG strains, as does overexpression of YdgT. As reported in an accompanying study (51), a nusA mutation associated with defective Rho-dependent termination is also suppressed by H-NS⌬64 and YdgT. These effects are manifest in strains that express wild-type H-NS, StpA or both proteins but not in strains that are simultaneously deficient for H-NS and StpA.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, expression of any one of several dominant-negative variants of H-NS, including ⌬64, L26P, and E53G/T55P, restores the efficiency of transcription termination (that is, suppresses polarity relief) in rho and nusG strains, as does overexpression of YdgT. As reported in an accompanying study (51), a nusA mutation associated with defective Rho-dependent termination is also suppressed by H-NS⌬64 and YdgT. These effects are manifest in strains that express wild-type H-NS, StpA or both proteins but not in strains that are simultaneously deficient for H-NS and StpA.…”
Section: Discussionmentioning
confidence: 67%
“…These results indicate that the effect of hns mutations on modulation of Rho-dependent termination is not completely correlated with that on transcription initiation or gene silencing. A search for genetic suppressors of the effects of H-NS on Rho-dependent termination, as reported in an accompanying study (51), also did not identify any H-NS-repressed gene as being responsible for such modulation. An alternative model is accordingly proposed below.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide gene expression patterns of NusA-deleted strains showed same pattern as that of the NusG-deleted ones, where the latter is a bona fide partner of Rho (6). More recently, a NusA mutant was observed to produce a termination defect at a Rho-dependent terminator, H-19B t R1 (17).…”
mentioning
confidence: 69%
“…In particular, the hairpin-dependent pauses are enhanced by NusA via stabilization of the hairpin-RNAP interaction (12). NusA improves the termination efficiency at many hairpin-dependent terminators by facilitating the hairpin folding (13) and also by stabilizing the latter's interactions in the RNA exit channel of the transcription elongation complex (14).Previously, different studies have indicated the involvement of NusA in the Rho-dependent termination process (15)(16)(17). A…”
mentioning
confidence: 99%
See 1 more Smart Citation